The Rhizome Essential Oil Composition of Zingiber officinale Roscoe. Core Collection from Northeast Indian Germplasm. Issue 4 (4th July 2022) - Begum, Twahira; Munda, Sunita; Baruah, Joyashree; Sarma, Neelav; Tamang, Raghu; Saikia, Samarjit; Haldar, Saikat; Lal, Mohan
Abstract: Zingiber officinale Roscoe. is a medicinally important plant with distinct aroma and pungency. The present study aims to evaluate the essential oil of 150 germplasm of ginger collected from different states across Northeast India which has been maintained at field gene bank. The rhizome essential oil was isolated by hydrodistillation using Clevenger apparatus and was evaluated by gas chromatography. The study revealed the presence of twenty-one chemical constituents in the studied germplasm out of which E-citral followed by Z-citral, 1, 8-cineole, ar-curcumene, camphene and geraniol were the major constituents. The identified minor compounds were 1-borneol followed by γ-muurolene, α-bisabolene, zingiberene, α-terpineol, farnesene, linalool, α-pinene, geranyl acetate, eudesmol and β-cedrene. This is the first report on the evaluation of essential oil constituents of diverse germplasm (150) of Z. officinale which will be highly beneficial for the identification of compound-rich germplasm of ginger. This would further pave the way for selection of ginger germplasm with superior trait in terms of chemical composition.